The Community Empowerment Policy to Lead A Clean and Healthy Life in Indonesia - Rr. Herini Siti Aisyah; M. Hadi Shubhan; Nur Basuki Minarno; Siswanto Siswanto; Sudarsono Sudarsono; Siswandi Hendarta; Raissa Virgy Rianda; Rama Azalix Rianda; Ahmad Munir; Heru Irianto (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Clean and Healthy Living Behavior (CHLB) is influenced by some factors such as knowledge, attitudes, economic status, and supports from health and social officers. Increasing the knowledge of CHLB in the household structure is very important. The regulation on Health Development Program concerns the guidelines for implementing healthy Indonesian programs with a family approach. Several obstacles involved the queue of patients, doctors, installation and emergency room, and working hours. This study aims to examine community empowerment policies for clean and healthy living behaviours, which are expected to be a solution to restrictions on several aspects of health facilities, increasing population and demands better service quality. The research method uses a socio-legal qualitative approach. Supporting Legal is collected. Field research is also conducted. In-depth interviews and FGDs carried out data collection. This study concludes that community empowerment is carried out using an educational approach involving community and religious leaders. Community empowerment aims to develop community knowledge and skills, use health facilities, and create health institutions that originate from the community. Critical awareness must be built by forming a Clean and Healthy Community Movement group to give the community a CHLB. Empowering people to live clean and healthy lives takes a long time and consistently. For this reason, there is a need for legal instruments that must be enforced strictly and with wisdom.